Maximum Total Irregularity of Totally Segregated Extended Bicyclic Graphs - Jorry, T. F. (Communications in Mathematics and Applications, 2022)
In this paper, we determine maximum total irregularity of two types of connected totally segregated bicyclic graphs on \(n\) vertices: extended \(∞\) bicyclic graph and \(Θ\)-bicyclic graph and also characterize those extremal graphs.